Modeling, design and experiments of a ball-screw inerter with mechanical diodes. (21st July 2021) - Yuehao, Li; Zhe, Cheng; Niaoqing, Hu; Yi, Yang; Zhuo, Xiao
Highlights: A new ball-screw inerter with mechanical diodes is proposed. The dynamical model and equivalent electrical model of a ball-screw inerter with mechanical diodes are established and analyzed. The structure vibration of the ball-screw inerter with mechanical diodes is smaller than the typical ball-screw inerter. Variable dampers exist in the ball-screw inerter with mechanical diodes. Abstract: To reduce the structure vibration caused by changes of working directions, this study proposes a ball-screw inerter with two mechanical diodes, which divides the rotary motion of the flywheel used in the ball-screw inerter into two unidirectional rotations. And the dynamical model and equivalent electrical model of a ball-screw inerter with two mechanical diodes are established and analyzed. Moreover, considering dissipation of energy caused by mechanical diodes, there is a damper in parallel with the inerter. And the damping factor of the damper is in direct proportion to the angular frequency of the exciting harmonic force, when one terminal is fixed and the amplitude of the exciting harmonic force is almost constant. On account of the model and analysis, a ball-screw inerter with two flywheels and two mechanical diodes is designed, manufactured, assembled and installed on the experiment rig. By analyzing the experimental data gathered by force sensor, acceleration sensor and laser displacement sensor, the conclusions that the ball-screw inerter with two mechanical diodes is able to reduce the impulse caused by changes of working directions and there is variable damper caused by mechanical diodes in parallel with the inerter are proved. Graphical abstract: Image, graphical abstract